Editorial: A Historical Focus on Comics. Issue 2 (1st September 2019) - Grove, Lawrence; Magnussen, Anne; Miller, Ann
Abstract : Comics history has been an integral part of comics research from the outset, but from the late 1980s and well into the 2000s, a historical focus seemed to live a more anonymous existence. This was largely due to the burgeoning and exciting interest in close analyses of comics as 'works', emphasizing the medium's potential as an art form. Over the past ten years, however, research interest into comics history has regained momentum, but this time combining classic comics history with a heightened awareness of the medium's aesthetic dimension and with some of the newer trends within historical research at large. The historical interest has been furthered by theoretical and methodological trends that reach beyond comics research. Inspired by anthropology and the linguistic turn, much historical research now has a pronounced focus on cultural products (such as comics) as part of society, and not only in cultural history in a strict sense but also in interaction with broader societal and political processes and conflicts. Within the comics field, this focus most obviously lends itself to some of the comics genres that have boomed within the past fifteen years, such as memory, documentary and 'activist' comics, but it is not limited to these. In its updated form, comics history research also follows another general trend within historical research, namely that of transnational studies, which questions a default national framework for understanding comics history and instead follows interaction and inspiration across national borders of industries and publications, as well as individual artists. As a third feature, the field has moved beyond the most widely studied countries and time periods and thereby questions the comics canon that usually evolves around North America and a limited number of European (and Asian) countries. All in all, comics history research is back from the margin, in a new and updated format.